'Give me liberty or give me Covid!': Anti-lockdown protests as necropopulist downsurgency. Issue 2 (4th May 2021) - Bratich, Jack
ABSTRACT: This paper examines the 'anti-lockdown' protests in the US beginning in April 2020 through the concepts of necropolitics (Mbembe) and microfascism (Deleuze and Guattari). The paper argues that these protests are examples of what it coins, necropopulism . What if the libertarian, hyper-individualistic, and reactionary populism we witness in these and other manifestations (e.g. mass shooters, alt-right street fights) are both fixated on their identity as a 'people, ' yet simultaneously indifferent to their own persistence? Examining the anti-lockdown and anti-masking protests and their precursors, the paper argues that microfascism is infused with homi-suicidal aesthetics. The essay seeks to refine our analysis when it comes to the cultural (necro)politics of this 'downsurgency, ' in which decline accelerates rapidly and might even be detached, ultimately, from its own demise. This analysis matters if we are to antagonize this necrotic force, not simply through a battle of ideas but by preventing a fascist social body from being fully activated and mobilized.